An optimized medial parapatellar approach to the goat medial femoral condyle - van Hugten, Pieter P. W. (Animal Model Exp Med, 2021)
Goats or sheep are the preferred animal model for the preclinical evaluation of cartilage repair techniques due to the similarity of the goat stifle joint to the human knee. The medial femoral condyle of the stifle joint is the preferred site for the assessment of articular cartilage repair, as this is the primary location for this type of lesion in the human knee. Proper surgical exposure of the medial femoral condyle is paramount to obtain reproducible results without surgical error. When applying the standard human medial arthrotomy technique on the goat stifle joint, there are some key aspects to consider in order to prevent destabilization of the extensor apparatus and subsequent postoperative patellar dislocations with associated animal discomfort. This paper describes a modified surgical technique to approach the medial femoral condyle of the caprine stifle joint. The modified technique led to satisfactory exposure without postoperative incidence of patellar luxations and no long‐term adverse effects on the joint.